ANALISA INVESTASI BISNIS BAHAN BANGUNAN - Dwi Sri Wiyanti (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2009)
AbstractTo face business competition, other than offers common building material, a building material store can offers design and construction of the building materials that have been bought. Market targets of the building material business are people that planned to build house or other building and property business stakeholder such as contractor, developer, and project owner. The increasing of projects these days bring good prospect for building material business, moreover if it is supported by the right market strategy. As long as there is a project, building materials will be needed. The purpose of this building material business is to gain profits as much as possible. With good organizing and high quality of human resources it will have a good prospect. With proper investment analysis based on positive calculation of Nett Present Value, more than one Benefit Cost Ratio value, and 900 million rupiahs of building material stocks, Break Event Point will be reached in the third year. Key word : Business, Store, Building materials